Telescopic Overdenture and Implant Supported Fixed Partial Denture: A Pragmatic Treatment Approach - Doğu Ömür Dede; M. Cenk Durmuşlar; Onur Şahın; Ayşegül Köroğlu; Özer İşısağ (Hindawi Limited, 2015)
This case report presents a patient who had been rehabilitated with a telescopic overdenture and implant supported fixed partial denture (ISFPD). The treatment process was as follows: (1) fabricating telescopic crowns and overdenture prosthesis for the lower jaw and a temporary complete denture for the upper jaw, (2) using the temporary denture as diagnostic and surgical guide to optimize dental implant placement, and (3) fabricating ISFPD for the upper jaw. Using the patient's existing or temporary denture not only serves as an alternative surgical guide to calibrate the dental implant locations but also helps to finish the restoration at desired dimension, size, and anatomic form.